Laser interference‐based technique for dynamic measurement of single cell deformation manipulated by optical tweezers. Issue 8 (23rd October 2018) - Liu, Jiaqi; Zhang, Fan; Zhu, Lianqing; Qu, Xinghua; Chu, Daping
Abstract: A laser interference‐based method was proposed to measure the deformation response of cell manipulated by optical tweezers. This method was implemented experimentally by integrating a laser illuminating system and optical tweezers with an inverted microscope. Interference fringes generated by the transmitted and reflected lights were recorded by a complementary metal oxide semiconductor camera. From the acquired images, cell height was calculated and cell morphology was constructed. To further validate this method, the morphological analyses of HeLa cells were performed in static state and during detachment process. Subsequently, the dynamic deformation responses of red blood cells were measured during manipulation with optical tweezers. Collectively, this laser interference‐based method precludes the requirement of complex optical alignment, allows easy integration with optical tweezers, and enables dynamic measurement of cell deformation response by using a conventional inverted microscope.